KEUNGGULAN PROGRAM TAHFIDZ DALAM MEMACU TINGKAT KECERDASAN SISWA DI MAN 2 KOTA BUKITTINGGI - Yulia Yulia; Bambang Trisno; Elfita Elfita (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research was written with the aim of examining the advantages of memorizing the Al-Qur'an in growing students' spiritual intelligence. The method used by researchers to study in this paper is a qualitative method with an analytical study which then produces several findings. First, cultivating spiritual intelligence is one method for solving the problem of a person's recent lack of morals. Second, the most effective way to grow a person's spiritual intelligence is through memorizing the Al-Qur'an because by memorizing the Al-Qur'an a person will always get closer to Allah. Third, memorizing the Al-Qur'an not only grows spiritual intelligence but can also grow emotional and intellectual intelligence. Fourth, those who memorize the Qur'an will essentially be influenced in their lifestyle, this is because they often mix it with the verses of Allah SWT. So that his lifestyle, mindset, personality and even behavior will be very similar to what is written in the Al-Qur'an which is his guide.